Turismo e seus discursos: percepção e atribuição na cidade de Caxias do Sul - RS - Dartora, Juliana de Souza (My University, 2014)
This study entitled: Tourism and its Speeches: Perception and Attribution in the city of Caxias do Sul/RS, reports on an exploratory research that has as objective to analyze perceptions that hotel workers in Caxias do Sul have about tourist activity in this city. In the theoretical part of the research, some Tourism concepts and implications are presented, beyond Social Psychology and its constructs attitude and perception, as well as Attribution Theory, basis for the study. The research, with qualitative data, investigates the perceptions of the subjects on Tourism, analyzing concepts, the relationship between tourism and Caxias do Sul, attributions of success or failure of Caxias do Sul in Tourism, as well as the attitude of hotel workers to Tourism. Previous results suggest that the subjects do not consider satisfactory the relationship between Caxias do Sul and the tourist activity, if the city is compared to neighbor towns, attributing, among other reasons, to the fact that other towns are constantly in the media e to the fact that the industrial activity is predominant in Caxias do Sul.
O presente estudo intitulado: Turismo e seus discursos: Percepção e Atribuição na Cidade de Caxias do Sul/RS, trata-se de uma pesquisa exploratória que tem por objetivo analisar as percepções que o trabalhador do setor hoteleiro de Caxias do Sul possui sobre o Turismo nesta cidade. No referencial teórico da pesquisa são apresentados os conceitos e premissas do Turismo, assim como da Psicologia Social e dos seus construtos percepção e atitude, além da Teoria da Atribuição, base teórica do estudo. A pesquisa de campo, de corte qualitativo, investiga a percepção dos sujeitos sobre o Turismo, englobando conceitos, a relação de Caxias do Sul com o Turismo, atribuições sobre o sucesso e/ou fracasso de Caxias do Sul para o Turismo e atitude dos trabalhadores em relação ao Turismo. Nos resultados da pesquisa, aponta-se que os sujeitos não consideram satisfatória a relação de Caxias do Sul com a atividade turística, quando a cidade é comparada a municípios vizinhos, atribuindo, entre outros fatores, ao fato que outros municípios estão permanentemente na mídia e ao fato da atividade industrial ser predominante em Caxias do Sul.
Keywords: Outros; Turismo; Pesquisa em Turismo; Atribuição; Percepção; Trabalhadores da hotelaria; Caxias do Sul (RS); Rio Grande do Sul; Tourism; Research in Tourism; Attribution; Perception; Hotel workers; Caxias do Sul (Brazil); Rio Grande do Sul (Brazil)